Novel mutations of the POLR3A gene caused POLR3-related leukodystrophy in a Chinese family: a case report - Shuiyan Wu; Zhenjiang Bai; Xingqiang Dong; Daoping Yang; Hongmei Chen; Jun Hua; Libing Zhou; Haitao Lv (BMC, 2019)
Abstract Background POLR3-related leukodystrophy is an autosomal recessive neurodegenerative disorder characterized by onset time ranging from the neonatal period to late childhood, progressive motor decline that manifests as spasticity, ataxia, tremor, and cerebellar symptoms, as well as mild cognitive regression and hypodontia. POLR3-related leukodystrophy belongs to the family of RNA polymerase III-related leukodystrophy, which are caused by biallelic mutations in the POLR3A, POLR3B, POLRC1, or POLR3K genes. Case presentation In this study, we report a female child with POLR3-related leukodystrophy manifesting as cognitive decline, moderate dysarthria, motor decline, cerebellar syndrome, short stature, dysphagia, hypodontia, and mild delayed myelination by brain imaging. Interestingly, polytrichia and bronchodysplasia were first observed in a POLR3-related leukodystrophy patient. Medical exome sequencing with high coverage depth was employed to identify potential genetic variants in the patient. Novel compound heterozygous mutations of the POLR3A gene, c.1771-6C > G and c.2611del (p.M871Cfs*8), were detected. One of them is an uncommon splice site mutation, and this is the first report of this mutation in a Chinese family. The father was determined to be a heterozygous carrier of the c.2611del (p.M871Cfs*8) mutation and the mother a heterozygous carrier of the c.1771-6C > G mutation. Conclusion The patient's newly emerged clinical features and mutations provide useful information for further exploration of genotype-phenotype correlations of POLR3-related leukodystrophy.